Didáctica de la tecnología e informática para la educación básica a través de proyectos - Poveda Pineda, Derly Francedy; Roberto Duarte, Dora Yanneth; Otálora Calderón, Betty Yaneth (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article pretends to describe the work the area of fundamentals and Didactics of Technology and Informatics on Basic Education training, the methodology is car- ried out by means of projects, taking into account the theoretical references which support the area based on curricular structure the didactics and the environments for its development. The students identify problems that can be susceptible of the development of a project taking into account the steps of a technological process. The articulation of theory and practice is obtained as a result during the develop- ment of the technology fair which has generated positive changes in concept and development of the area, as fundamental basis on thought processes, so that its importance is analyzed in educative institutions, by answering the different contexts and necessities.